2017
DOI: 10.1038/s41598-017-02604-4
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of angiogenesis-specific signalling in adult testis results in xenograft degeneration

Abstract: Ectopic xenografting of testis is a feasible option for preservation of male fertility and angiogenesis plays a pivotal role in xenograft survival and functionality. When compared to immature testis, the adult testis is unable to establish functional xenografts due to potentially lower efficiency to induce angiogenesis. The precise molecular mechanism, however, remains elusive. In the present study, we compared adult and immature testis xenografts for survival, maturation and germ cell differentiation. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
3
8
0
Order By: Relevance
“…However, the absence of elongated spermatids in the xenografted testis indicated that the spermatogenesis remained incomplete. These results are consistent with previous reports in which incomplete spermatogenesis was reported in xenografted rat testis at 8-wk post-grafting with a spermatogenic arrest at pachytene-stage spermatocytes 8 , 9 . Spermatogenesis was observed to remain incomplete even after an extended grafting period (12 wk; data not shown).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the absence of elongated spermatids in the xenografted testis indicated that the spermatogenesis remained incomplete. These results are consistent with previous reports in which incomplete spermatogenesis was reported in xenografted rat testis at 8-wk post-grafting with a spermatogenic arrest at pachytene-stage spermatocytes 8 , 9 . Spermatogenesis was observed to remain incomplete even after an extended grafting period (12 wk; data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…Following xenografting, immature rat testis showed a progressive increase in weight over 8 wk, suggestive of consistent growth of seminiferous tubules and supporting cellular structures 19 and establishment of an effective vascular connection between the xenograft and the recipient, resulting in its survival 8 . Similarly, a progressive increase and subsequent restoration of the recipient’s seminal vesicle weight, an indicator of circulating bioactive testosterone 8,16,1923 , suggests that not only the spermatogenic but also the steroidogenic function of the immature rat testis was recovered in the xenografts. This also indicates that the donor tissue responded to gonadotrophin stimulation of the recipient mice.
Figure 7A model for spermatogenic arrest in xenografted testis.
…”
Section: Discussionmentioning
confidence: 99%
“…In patients with testicular tumor or infertility, abnormal activity of signaling pathways was observed, including the Wnt signaling pathway, the PI3k/Akt signaling pathway, etc 56,[132][133][134][135][136][137] . We had discussed of the TGF-β/Smad, AMPK, and MAPK signaling pathways in SCs to regulate normal spermatogenesis.…”
Section: Pathways and Potential Clinical Applications Of Abnormal Spementioning
confidence: 99%
“…The formation of new blood vessels is fundamental to health and disease[1,2,3,4,5]. This formation can occur by two processes: vasculogenesis or angiogenesis.…”
Section: Introductionmentioning
confidence: 99%